On perspectives of Russian-Georgian dialogue on the issue of reburial of kings Vakhtang VI and Teimuraz II - M. A. Volkhonsky; V. M. Mukhanov (Международная аналитика)
After removal of M. Saakashvili from the Georgian political scene, a progress in relations between Russia and Georgia can be observed. In this context, the wide attention has been drawn to the issue of reburial of the Georgian kings Vakhtang VI and Teimuraz II. The article discusses the negotiation process, lasted from 2002 to 2014, between the Georgian Church and the Russian Church concerning the transfer of the remains of the Georgian kings, as well as the motives, goals and arguments of the parties. An analysis of the negotiations has led to the conclusion that the issue of reburial has two key aspects – political and moral-ethical. The requirement of the Georgian Church to carry the remains of Vakhtang VI and Teimuraz II from Russia to Georgia is part of its overall policy aimed to strengthen its prestige and authority Kin Georgian society. For the Russian side, this action promises nothing more than image losses. As for ethical aspects, the references of the Georgian side to the kings’ will to be buried in their homeland are not supported by authentic documents. At the moment, it remains an open question requiring further research.